Oxidant and antioxidant status of police officer in the city and rural area (Medical Journal of Indonesia, 2004)
This study was designed to investigate the biochemical alteration in human caused by free radical accumulation due to air pollution. The policemen recruited were 60 country policemen consisting of 30 non smokers (group I) and 30 smokers (group II); 30 smoking policemen with administrative work in Jakarta (group III) and 30 smoking traffic policemen from Jakarta (group IV). Our results show that the plasma malondialdehyde (MDA) contents of groups I, II, III, IV, respectively were : 3.34 ± 0.81 umol/l; 4.28 ± 0.77 umol/l; 5.20 ± 0.66 umol/l and 5.12 ± 0.78 umol/l which were statistically different (p < 0.01) among each others, except between groups III and IV. The activity of superoxide dismutase (SOD) of the groups respectively, were: 16.75 ± 9.80 U/mg protein; 22.83 ± 6.82 U/mg protein; 26.10 ± 8.50 U/mg protein and 26.90 ± 9.34 U/mg protein, which were statistically different (p < 0.05) between group I vs the other groups. The catalase activity of the groups respectively were : 106.25 ± 47.47 U/mg protein; 118.84 ± 42.73 U/mg protein; 119.83 ± 35.35 U/mg protein and 145.57 ± 61.85 U/mg protein. The statistical difference (p < 0.05) was found between group I & IV. Administration of vitamins C (500 mg) and E (300 mg) daily for 30 days to the policemen with high oxidant stress caused a decreased in the activities of SOD from 27.34 ± 10.05 U/mg protein to 16.91 ± 6.51 U/mg protein (p < 0.05) and catalase from 134.29 ± 53.28 U/mg protein to 67.07 ± 25.26 U/mg protein (p < 0.05). This study shows us that the oxidant status of city policemen was higher than that of rural policemen and that a combination of vitamins C & E could reduce the oxidant stress to a certain extent. (Med J Indones 2004; 13: 77-80) Keywords: malondialdehyde, superoxide dismutase, catalase, population study.